The The Influence of Health Education Through Audio Visual Media on Knowledge of Coronary Heart Disease in Posbindu PTM Clients - Yulta Kadang; Cicilia Nony Ayuningsih Bratajaya; Previarsi Rahayu; Ananda Patuh Padaallah (An Idea Health Journal, 2024)
Cardiovascular disease (CVD) is one of the health problems that contributes to the largest number of deaths in the world which is defined as an abnormal condition of the heart and blood vessels, one of which is coronary heart disease (CHD). This study was conducted with the aim of analyzing whether there is an effect of Health Education through Audiovisual on Client Knowledge about Coronary Heart Disease at the PTM Posbindu at the Tambelang Health Center UPTD, Bekasi Regency. The type of quantitative research used in this study is Quase Experimental Design with the One Group Pretest and Posttest approach. The location of the study was at the PTM Posbindu UPDT Tambelang Health Center, Bekasi Regency and was carried out in August 2024. Sampling was carried out using non-probability sampling using the purposive sampling method. The sample used was 21 PTM Posbindu clients. The questionnaire used was first tested for validity and reliability with Alpha Cronbach 0.742 which showed that this questionnaire could be used to measure knowledge about coronary heart disease. The data were analyzed using the Wilcoxon alternative test because the results of the ShapiroWilk normality test were not normally distributed